Quantitative analysis of COH fluids synthesized at HP–HT conditions: an optimized methodology to measure volatiles in experimental capsules. Issue 5 (16th September 2016) - Tiraboschi, C.; Tumiati, S.; Recchia, S.; Miozzi, F.; Poli, S.
Abstract: The quantitative assessment of COH fluids is crucial in modeling geological processes. The composition of fluids, and in particular their H2 O/CO2 ratio, can influence the melting temperatures, the location of hydration or carbonation reactions, and the solute transport capability in several rock systems. In the scientific literature, COH fluids speciation has been generally assumed on the basis of thermodynamic calculations using equations of state of simple H2 O–nonpolar gas systems (e.g., H2 O–CO2 –CH4 ). Only few authors dealt with the experimental determination of high‐pressure COH fluid species at different conditions, using diverse experimental and analytical approaches (e.g., piston cylinder + capsule piercing + gas chromatography/mass spectrometry; cold seal + silica glass capsules + Raman). In this contribution, we present a new methodology for the synthesis and the analysis of COH fluids in experimental capsules, which allows the quantitative determination of volatiles in the fluid by means of a capsule‐piercing device connected to a quadrupole mass spectrometer. COH fluids are synthesized starting from oxalic acid dihydrate at P = amb and T = 250°C in single capsules heated in a furnace, and at P = 1 GPa and T = 800°C using a piston‐cylinder apparatus and the double‐capsule technique to control the redox conditions employing the rhenium–rhenium oxide oxygen buffer. A quantitative analysis of H2 O, CO2, CH4, CO, H2, O2, and N2 along with associated statistical errors is obtained by linear regression of the m / z data of the sample and of standard gas mixtures of known composition. The estimated uncertainties are typically <1% for H2 O and CO2, and <5% for CO. Our results suggest that the COH fluid speciation is preserved during and after quench, as the experimental data closely mimic the thermodynamic model both in terms of bulk composition and fluid speciation.